(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: In this modern world yoga become the popular activity across the world. This bibliometric analysis aimed to provide a systematic review analysis in the field of Sports Science on yoga research publication. Objectives: In this bibliometric analysis used to find the information about the yoga related research publication done in the sports science. Methods: Web of science database used to gather the data regarding yoga in the sports science field. By using the various keyword related to the terms of “Yoga”. Based on the inclusion and exclusion criteria the data were finalized and expert in the plain text file format. The export document analysis in the R studio (Biblioshiny) software. Results: From this bibliometric analysis we come to know very few studies only conducted in the field of sports science to improve the sports performance and fitness abilities.